"Capitalizing on the Wealth Buried Deep Within Living Matter," or Politics and Patents - Horsley, Jane (UnderCurrents: Journal of Critical Environmental Studies, 1993)
The intellectual property rights have become the mechanism of choice for "capitalizing on the wealth buried deep within living matter" by providing patents and copyrights in the products and processes of biotechnology. The most infamous of these developments was the U.S. Patent for the "Transgenic Mouse’ - a mouse genetically engineered for a particular oncogene, "enabling it to get cancer on demand." [...]